Polisemi Kata Kiken Dalam Portal Berita Online NHK Yasashii Kotoba Nyuusu: Kajian Semantik - Aminulloh, Aminulloh; Anwar, Aulia Arifbillah (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2026)
Polysemy is a central issue in semantic studies, referring to a single lexical item that carries multiple related meanings depending on context. In Japanese, this phenomenon is known as tagigo (多義語). The word kiken (危険), commonly translated as “danger” or “risk,” demonstrates semantic variation across different text genres. This study aims to identify the core meaning and extended meanings of kiken and to analyze the semantic relations underlying its meaning expansion in NHK Yasashii Kotoba Nyuusu. This research employs a qualitative descriptive method with a semantic analysis approach. The data consist of sentences containing kiken extracted from 12 news articles published between August 2024 and July 2025. A total of 27 instances were identified and classified based on their semantic categories. The findings reveal that 8 data represent the core meaning, referring to direct physical danger to body and life. Meanwhile, 19 data demonstrate extended meanings, including social and ecological risks as well as the potential occurrence of undesirable or life-threatening events. The semantic expansion is influenced by figurative relations, particularly metonymy, as well as metaphor and synecdoche. The study concludes that the meaning of kiken is highly contextual and dynamic, reflecting semantic flexibility in Japanese news discourse. These findings highlight the importance of contextual interpretation in understanding polysemous vocabulary, especially in high-context languages such as Japanese.